Truth and Scepticism: Developing Bildung and Phronesis through Socratic Questioning - Nicholson, Garry (Philosophical Inquiry in Education)

(untitled) (Canadian Philosophy of Education Society, 2022)
This research paper considers the place of the European lifelong-learning philosophical concept of Bildung (self-formation) and how Socratic questioning activities might be used to facilitate its development. Originating with the great philosophical thinkers of the German Renaissance, it is a concept that is again attracting attention because of its focus on developing the “whole” person and its potential for developing phronesis “practical wisdom.” The primary source of research data is a podcast in which a diverse group of BAME (Black, Asian, and minority ethnic) learners discuss COVID-19 vaccinations from their own cultural perspectives through a Socratic dialogue. During this process, Bildung was developed by participants recognizing mutual concerns during this process, and Gadamer’s (1960/1989) hermeneutic dialectical concept known as the “Fusion of Horizons” was played out. The dialogue identifies “trust” as an essential moral value and one that is needed in any just and stable society. This research suggests an alternative educational paradigm should be realised that lends itself better to developing Bildung and phronesis. The implications of this for teacher training are discussed and why it is important to develop “phronetic” educators. Reference is made to what this might look like in reality by highlighting the use of Socratic questioning in Danish folk high schools and how they have made the philosophical concept of Bildung central to their mission.